Optimising Arabic Language Learning Management: Digitalisation Efforts - Ahmadi Ahmadi; Aulia Mustika Ilmiani; Rita Febrianta; Mohamed Daud (Universitas Islam Negeri Palangka Raya, 2024)
The background of this research includes the complexity of challenges in managing Arabic language learning, especially with limited resources and the massive development of digital technology. This study aims to identify the strategies and steps the Head of the study program took in utilizing technology to digitalize Arabic language learning. This research methodology uses a qualitative approach with data collection techniques through in-depth interviews with the Head of the study program and participatory observation of the digitalization efforts made. The results obtained from the research show that there are three stages of digitalization efforts. First, the collaboration between Arabic Language Education lecturers is planned to revise the curriculum and upgrade semester implementation plans. Second, implementation should be done using interactive Arabic learning models and technology-based learning media. Third, monitoring the learning process between lecturers and students, student learning progress, reviewing the results of midterm and final semester exams and facilitating communication between lecturers and students regarding learning problems. Hopefully, this research can provide recommendations for other educational institutions in optimizing Arabic language learning management.